Website-Based Academic Information System at SMA Negeri 1 Lubai, Muara Enim Regency, Using Extreme Programming - Nanda Febriansyah (Institute of Information Technology and Social Science (IITSS), 2024)
Rapid technological progress has encouraged educational institutions to exploit digital innovations that enhance academic administration and institutional competitiveness. Academic information systems (AIS) provide structured management of student, teacher, registration, and grade data while simultaneously supporting school promotion. SMA Negeri 1 Lubai still maintains its academic records manually, a process that limits efficiency, accessibility, and transparency. With 574 students distributed across 10 classes, the school requires a website-based AIS capable of handling academic data and providing public access to institutional information. This study designs and develops a web-based academic information system for SMA Negeri 1 Lubai employing the Extreme Programming (XP) methodology a lightweight agile framework suitable for small teams facing evolving requirements. The system enables efficient storage, retrieval, and dissemination of academic information, improving administrative performance and accessibility for teachers, students, and the general public.